2019
DOI: 10.1111/tbed.13432
|View full text |Cite
|
Sign up to set email alerts
|

Improving Village Animal Health Worker participation in national disease surveillance systems: A case study from Cambodia

Abstract: Para‐veterinary systems have arisen in numerous developing countries to address the low capacity of national veterinary services in meeting livestock health demands of mainly smallholder farmers. In Cambodia, the village animal health worker (VAHW) system was established in the early 1990s, involving short training programmes to equip VAHWs to provide basic animal health services for smallholder farmers, particularly the vaccination of cattle for haemorrhagic septicaemia (HS). However, there are increasing exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 17 publications
2
32
0
Order By: Relevance
“…The majority of VAHWs provided their animal health services to large ruminants rather than pigs or poultry, and these findings were similar to the previous reports from Cambodia (Bhandari et al, 2011;MacPhillamy et al, 2019;Stratton et al, 2015) and northern Malawi (Huttner, Leidl, Jere, & Pfeiffer, 2000). It should be noted that although VAHWs may wish to provide animal health services to poultry, farmers generally do not think it worthwhile spending money for low-value village poultry.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The majority of VAHWs provided their animal health services to large ruminants rather than pigs or poultry, and these findings were similar to the previous reports from Cambodia (Bhandari et al, 2011;MacPhillamy et al, 2019;Stratton et al, 2015) and northern Malawi (Huttner, Leidl, Jere, & Pfeiffer, 2000). It should be noted that although VAHWs may wish to provide animal health services to poultry, farmers generally do not think it worthwhile spending money for low-value village poultry.…”
Section: Discussionsupporting
confidence: 83%
“…This is consistent with a previous study from 2008 that identified most VAHWs (66%) from 19 provinces earned less than 40% of their household income from animal health and vaccination services (Stratton et al, 2015). However, a 2015 survey of VAHWs from Takeo and Tbong Khmum provinces identified that although incomes from VAHW activities were also generally low with monthly incomes predominantly within the USD 48.80 -USD 97.50 income bracket (38%), 62% of VAHW earning over USD 97.50/month had over 10 years of VAHW experience, and there also appeared to be a strong association between income generating activities and frequency of contact with district animal health authorities (MacPhillamy et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent report from neighboring Cambodia, almost 90% of surveyed village animal health workers from two provinces admitted that they used antibiotics to treat FMD-affected animals. 12 In addition to antibiotics, affected animals may be treated with mild disinfectants, occasionally anti-inflammatory drugs, and in many rural communities in Laos, lesions may be treated with traditional therapies, including application of lemon juice or the scraping of lesions with the bark of trees. 3,7 In other countries, anecdotal reports include the use of soda-ash solution for washing the lesions and application of honey and various astringent substances (PW, personal observations).…”
Section: Introductionmentioning
confidence: 99%